Formulasi Emulgel Antiinflamasi dari Ekstrak Temulawak (Curcuma xanthorrhiza Roxb) - Radhia Riski, Abdul Halim Umar, Rismadani (STIFA Makassar, 2016)
Ginger extract are known to have antiinflamatory effect at a dose of 200 mg. In order to be applied to the skin, ginger extract must be formulated into stable emulgel. This study aims to formulate and evaluate the physical stability of emulgel from ginger extract using carbomer® 940 as gelling agent with concentration variation 0,5%, 1%, 1,5% and 2%. Physical stability evaluation was conducted including organoleptic test, pH, spreading test, adhesion test and viscosity test. From the research result it is obtained yellow and distinctive odor of emulgel. pH of all emulgel formula were 6. Adhesion test result of formula 5, 6, 7, 8 were 00.63, 19.03, 50.84 and 60.50 respectively. Spreading test result from formula 5, 6, 7, 8 were 5,725, 4,875, 4,325 and 3,85 respectively. Viscosity test result were 2.200, 3.720, 4.000 and 7.720 for formula 5, 6, 7 and 8 respectively. According to paired sample T-test there was not significant differences between formula on pH test, viscosity test, adhesion test (p>0,05), before and after accelerated storage condition. In spreading test result showed a significant difference 0,000 (0<0,05) before and after accelerated storage condition.